Foldable Detergents for Membrane Protein Stability - Youn,T; Yoon,S; Byrne,B; Chae,PS (ChemBioChem: a European journal of chemical biology, 2022)
Detergents are widely used for membrane protein structural study. Many recently developed detergents contain multiple tail and head groups, which are typically connected via a small and branched linker. Due to their inherent compact structures, with small inter-alkyl chain distances, these detergents form micelles with high alkyl chain density in the interiors, a feature favorably associated with membrane-protein stability. A recent study on tandem triazine maltosides (TZMs) revealed a distinct trend; despite possession of an apparently large inter-alkyl chain distance, the TZM−Es were highly effective at stabilizing membrane proteins. Thanks to the incorporation of a flexible spacer between the two triazine rings in the linker region, these detergents are prone to folding into a compact architecture in micellar environments instead of adopting an extended conformation. Detergent foldability represents a new concept of novel detergent design with significant potential for future detergent development.